Diversity of aquatic insects and their functional feeding group from anthropogenically disturbed streams in Mae sot district, Tak province, Thailand - Thanee I. (2014)
Diversity and aquatic insect functional feeding groups were studied from 10 study sites in Mae Sot District, Tak Province, Thailand. The aquatic insects were collected using functional feeding group ratio (FFG) to evaluate the ecological conditions of cadmium- contaminated streams. The FFG ratio indicated that most of the 10 sites were highly heterotrophic sites and the site MaeTao (MT) 3 was the least heterotrophic site. Nevertheless, site MT 3 was indicated as autotrophic sites in the rainy season. Site MT 1 represented the highest autotrophic site but the other sites had the worst linkage between the riparian vegetation and stream ecosystem function, which was indicated by shredder populations. Sites MT 1 and 2 provided the strongest support for populations of filtering collectors, whereas sites MT 4, 5, 6 and Mae Ku (MK) 3 indicated an inadequate support for filtering collectors. Sites MT 1, 2, 3, 4 and MK 1, 2 performed as high stable habitats. Seasonal change affected the predator and prey ratio, but it was found that in the hot season, a number of predators were not abundant when compared with the other seasons.